Auditoría de Seguridad Vial, en la Unidad Funcional 2: Asia – Tres Puertas (Concesión Pacifico 3), desde el Km 0+000 al Km 3+664 y del Km 7+400 al Km 13+000 - Galeano Uribe, John Edwar; Quintero García, Daniel Stiven; Ramírez Herrera, Juan David (Universidad Antonio Nariño, 2023)
In the present study, a Road Safety Audit (RSA) was conducted on the road segment known as Asia - Tres Puertas (Pacific 3 Concession), covering from kilometer 0+000 to kilometer 3+664 and from kilometer 7+400 to kilometer 13+000.